Importance Level of Success Criteria in Management Consulting Operations: Th e Turkish Case - Arantes, Sitki Gozlu; Coskun, Aylin (Brazilian Journal of Operations & Production Management, 2010)
The purpose of this study is to determine the importance level of success criteria in management consulting operations in Turkey. A survey instrument was developed and posted on the Internet in order to reach as more respondents as possible for the study. A Likert scale of 10 was chosen to explain precisely the differences between the criteria. Eighty responses were returned. It should be stated that the respondents of the survey were all Turkish consultants. Descriptive statistical analyses were conducted for the four main categories and their criteria. On the basis of a literature search, it was found reasonable to classify the success criteria for management consulting operations into four basic categories such as human resources, competitiveness, customer relations, and processes and methods. The study presents the ratings of four basic categories and their criteria, which essentially affect the success of consulting fi rms. The results of the research will serve consulting companies as guidelines to pinpoint improvement areas in their consultancy operations. The responses received from the consultants can be considered reliable and satisfactory. In addition, the important point that this study has revealed is the interest and willingness of the consultants for further studies.